Learning the hard way : masculinity, place, and the gender gap in education - Morris, Edward W., 1973- (Rutgers University Press, 2012)
In Learning the Hard Way, Edward W. Morris explores and analyzes detailed ethnographic data to examine the purported gender gap between boys and girls in educational achievement at two low-income high schools-one rural and predominantly white, the other urban and mostly African American. He explains how race, class, and geographic location combine to influence and complicate the construction of gender identities in high school students and affect the respective academic performance of the stud.
Title from PDF title page (viewed on August 30, 2012).
Keywords: Sex differences in education -- United States -- Case studies.; High school boys -- United States -- Social conditions -- Case studies.; Men -- United States -- Identity -- Case studies.; Black people -- Race identity -- United States -- Case studies.; Academic achievement -- United States -- Case studies.; Différences entre sexes en éducation -- États-Unis -- Études de cas.; Hommes -- États-Unis -- Identité -- Études de cas.; Personnes noires -- Identité ethnique -- États-Unis -- Études de cas.; EDUCATION -- Educational Psychology.; SOCIAL SCIENCE -- Sociology -- General.; Academic achievement; Black people -- Race identity; Men -- Identity; Sex differences in education; United States; Case studies